A Conceptual Model for Safety Management Systems (SMS) Practices among Employees in the Manufacturing Industry - Ab Rahman, Suzana; Naseri, Roszi Naszariah Nasni; Ishak, Nadiah (Information Management and Business Review, 2024)
The burgeoning manufacturing sector has been the primary driver of Malaysia’s substantial and notable economic expansion. Notwithstanding these, the Malaysian manufacturing sector remains afflicted by concerning safety concerns. To enhance the situation, the Malaysian government has proposed the use of self-regulatory safety management systems (SMS). However, there are doubts about the employees’ preparedness to adopt this measure. Implementing SMS has numerous complexities. Despite progress made in the SMS technique, failures continue to be prevalent. There is a lack of literature regarding the perspectives of the manufacturing industry regarding their concerns regarding the implementation of SMS. This study aimed to ascertain the presence of safety practices derived from SMS elements and identify the characteristics associated with the successful application of SMS. The anticipation is that the outcomes of this study will contribute to the successful implementation of SMS. The findings of this research will be of significant importance to the stakeholders and policymakers.